Focal Arrhythmia Ablation Determined by High‐Resolution Noninvasive Maps: Multicenter Feasibility Study. (July 2015) - HOCINI, MÉLÈZE; SHAH, ASHOK J.; NEUMANN, THOMAS; KUNISS, MALTE; ERKAPIC, DAMIR; CHAUMEIL, ARNAUD; COPLEY, SHAHNAZ‐JAMIL; LIM, PHANG BOON; KANAGARATNAM, PRAPA; DENIS, ARNAUD; DERVAL, NICOLAS; DUBOIS, RÉMI; et al.
Rapid Mapping and Ablation Using a Novel Platform Introduction A noninvasive 3D mapping technique (ECVUE™, CardioInsight Inc., Cleveland) maps the origin and mechanisms of various arrhythmias without catheterizing the heart. Methods Thirty‐three patients (3 centers, mean 45.0 ± 14.6 years, ) with symptomatic premature ventricular complexes (24 PVCs), focal atrial tachycardias (2 ATs), and manifest accessory pathways (7 WPW syndromes) were prospectively explored using 3D, noninvasive bedside electrocardiomapping. The location of origin of the focal arrhythmia was first determined using noninvasive mapping. Subsequently, a stimulus artifact was delivered at this site to confirm and evaluate the precise location of the mapped focal origin. The procedural parameters and clinical efficacy were studied. Results Ablation was successful in 32/33 (97%) patients (PVCs: 13 right, 10 left, 1 septal; WPW: 3 left, 3 right; ATs: 2 left) without complications. The time from catheterization to permanent arrhythmia elimination/termination, RF duration, skin‐to‐skin procedural duration, and fluoroscopic exposure were median 16, 3.98, 71, and 11.9 minutes (for n = 29), respectively. At mean 24.7 ± 3.7 months of follow‐up, 31 patients remain arrhythmia‐free after a single procedure. One patient (right WPW syndrome) required repeat ablation 1 month later. One patient had recurrence of PVCs and is now deceased. The cumulative radiation (CT scan and fluoroscopy) exposure was median 7.57 mSv. Conclusion ECVUETM is a noninvasive tool allowing rapid preprocedural localization of focal arrhythmia and enables the electrophysiologist with highly specific information to direct RF delivery at the source of the arrhythmia with minimal intracardiac mapping.